103k views
2 votes
Drag the correct steps into order to evaluate 42 + t6 for t = 12.

User Qinsi
by
4.8k points

2 Answers

3 votes

Answer:

1. 42 + t/6

2. 42 + 12/6

3. 42 + 2

4. 44

Explanation:

-You start of with 42 + t/6. If t = 6

-If t = 6, the next step should be to replace t with 12 So it would be 42 + 12/6.

-If we have 12/6 we know to divide. 12 divided by 6 is 2. So we would replace 12/6 with 2. Now we have 42 plus 2

-42 plus 2 is 44.

User Synaptik
by
5.5k points
4 votes

Answer:

42+ (12)6=

42+72=114

Explanation:

use pemdas to eliminate parethesis then add them together

User Volkan Ulukut
by
5.4k points